Field Study of the Possible Effect of Parental Irradiation on the Germline of Children Born to Cleanup Workers and Evacuees of the Chornobyl Nuclear Accident. Issue 12 (2nd July 2020) - Bazyka, Dimitry; Hatch, Maureen; Gudzenko, Natalia; Cahoon, Elizabeth K; Drozdovitch, Vladimir; Little, Mark P; Chumak, Vadim; Bakhanova, Elena; Belyi, David; Kryuchkov, Victor; Golovanov, Ivan; Mabuchi, Kiyohiko; et al.
Abstract: Although transgenerational effects of exposure to ionizing radiation have long been a concern, human research to date has been confined to studies of disease phenotypes in groups exposed to high doses and high dose rates, such as the Japanese atomic bomb survivors. Transgenerational effects of parental irradiation can be addressed using powerful new genomic technologies. In collaboration with the Ukrainian National Research Center for Radiation Medicine, the US National Cancer Institute, in 2014–2018, initiated a genomic alterations study among children born in selected regions of Ukraine to cleanup workers and/or evacuees exposed to low–dose-rate radiation after the 1986 Chornobyl (Chernobyl) nuclear accident. To investigate whether parental radiation exposure is associated with germline mutations and genomic alterations in the offspring, we are collecting biospecimens from father-mother-offspring constellations to study de novo mutations, minisatellite mutations, copy-number changes, structural variants, genomic insertions and deletions, methylation profiles, and telomere length. Genomic alterations are being examined in relation to parental gonadal dose, reconstructed using questionnaire and measurement data. Subjects are being recruited in exposure categories that will allow examination of parental origin, duration, and timing of exposure in relation to conception. Here we describe the study methodology and recruitment results and provide descriptive information on the first 150 families (mother-father-child(ren)) enrolled.